2008
DOI: 10.1624/105812408x364152
|View full text |Cite
|
Sign up to set email alerts
|

Effective Antenatal Education: Strategies Recommended by Expectant and New Parents

Abstract: Antenatal education is a crucial component of antenatal care, yet practice and research demonstrate that women and men now seek far more than the traditional approach of a birth and parenting program attended in the final weeks of pregnancy. Indeed, women and men participating in this study recommended a range of strategies to be provided during the childbearing year, comparable to a ''menu in a restaurant.''

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0
3

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 14 publications
3
40
0
3
Order By: Relevance
“…Parents, on the other hand, reported that they preferred not only well-structured content but also an interactive learning approach; specifically, more group activities and more discussions with other parents. These findings regarding parental preferences are in line with the findings of previous studies (Ahldén et al, 2012;Schrader McMillan et al, 2009;Svensson, Barclay, & Cooke, 2008).…”
Section: Group Leaders' Approaches To Presenting Contentsupporting
confidence: 92%
See 1 more Smart Citation
“…Parents, on the other hand, reported that they preferred not only well-structured content but also an interactive learning approach; specifically, more group activities and more discussions with other parents. These findings regarding parental preferences are in line with the findings of previous studies (Ahldén et al, 2012;Schrader McMillan et al, 2009;Svensson, Barclay, & Cooke, 2008).…”
Section: Group Leaders' Approaches To Presenting Contentsupporting
confidence: 92%
“…These advantages accrue at least in part from the scaffolding process, a process in which group members act as resources for each other and help other group member's progress in their understanding. One group of researchers has reported that expectant and new parents prefer a menu of learning strategies that includes lectures from experts; small group, problem-solving discussions; and social groups for the development of support networks (Svensson et al, 2008).…”
Section: Group Leaders' Approaches To Presenting Contentmentioning
confidence: 99%
“…A systematic review of the evidence on antenatal education shows that while research is limited parents wanted information and support matched in a timely way to the milestones of the developing baby (Schrader et al, 2009). Expectant and new parents' needs are in relation to parenting skills rather than receiving large amounts of information (Svensson et al, 2008). The needs of expectant parents are not always met where antenatal education classes may be large with the emphasis on the educators' priorities in terms of education topics rather than parents need for information on parenting (Koehn 2002).…”
Section: Discussionmentioning
confidence: 99%
“…It has long been recommended that infant CPR training should be provided to parents, babysitters and child care providers (Cyr, 2012).While infants are less likely to survive out of hospital cardiac arrest, paediatric basic life support involving community effort and early CPR provides the best chance of survival (Berg et al, 2010). Learning skills rather than information transfer has been identified as a particular need of expectant parents in relation to antenatal education (Svensson et al, 2008). Learning the skills of infant CPR and what to do in the event of an infant choking has particular relevance for expectant and new parents as they begin their transition to parenthood.…”
Section: Introductionmentioning
confidence: 99%
“…Antenatal classes and programs are more common nowadays, offered by any individuals or organizations with the objectives to help the mothers or both parents to prepare towards birth and parenthood transition [15][16][17]. It is mostly impossible to make each and every program similar in its content but it is suggested that the education program does not only focus on one part of the postpartum issues only, rather to provide a wide range of knowledge about other postpartum issues including the psychosocial adjustment and emotional well-being of the parents.…”
Section: Conclusion Implication For Future Practicementioning
confidence: 99%